2020
DOI: 10.1186/s12876-020-01362-4
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic undifferentiated carcinoma with osteoclast-like giant cells curatively resected after pembrolizumab therapy for lung metastases: a case report

Abstract: Background: Therapy targeting programmed death-1 or programmed death-1 ligand-1 (PD-1/PD-L1) has been developed for various solid malignant tumors, such as melanoma and non-small-cell lung cancer (NSCLC), but this approach has little effect in the treatment of pancreatic cancer. Pancreatic undifferentiated carcinoma with osteoclast-like giant cells (UCOGC) is a rare pancreatic malignancy having unique morphology and is considered a variant of pancreatic ductal adenocarcinoma (PDAC). Although UCOGC has been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…These insights might have potential impact for therapeutic strategies and suggest a strong need for a clinical trial of immune checkpoint immunotherapy in patients with advanced PD-L1 positive UC-OGC. Such immunotherapy may also exert antitumor effects on distant metastases of UC-OGC, as recently shown (75).…”
Section: Prognosis and Treatmentmentioning
confidence: 81%
“…These insights might have potential impact for therapeutic strategies and suggest a strong need for a clinical trial of immune checkpoint immunotherapy in patients with advanced PD-L1 positive UC-OGC. Such immunotherapy may also exert antitumor effects on distant metastases of UC-OGC, as recently shown (75).…”
Section: Prognosis and Treatmentmentioning
confidence: 81%
“…Finally, we read with interest a recent publication by Obayashi et al 27 about a similar patient in whom pulmonary metastases from UCOCG pancreatic cancer responded to checkpoint inhibitors. However, TMB was not assessed in this patient, and the patient received treatment meant for a presumed lung cancer.…”
Section: Discussionmentioning
confidence: 98%
“…PD‐L1 could prove be an effective predictive marker for novel immunotherapy with immune checkpoint inhibitors (Pembrolizumab) especially in patients with advanced stage UCOGC 20 . Pembrolizumab monotherapy was highly effective for metastatic lung lesions after curative resection of pancreatic UCOGC 21 …”
Section: Discussionmentioning
confidence: 99%
“…20 Pembrolizumab monotherapy was highly effective for metastatic lung lesions after curative resection of pancreatic UCOGC. 21 Currently there are no standard guidelines for the management of UC-OGC. En-bloc curative resection in early stages is the main line treatment, but most studies have shown disappointing results in unresectable cases with survival of less than 1 year.…”
Section: Case Reportmentioning
confidence: 99%